Correction to: Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; de Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
The article: Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections, written by Hussein Wazneh, Philippe Gachon, René Laprise, Anne de Vernal, Bruno Tremblay was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 5 January 2021 without open access.
Keywords: Gachon_Philippe

Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; de Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
Atmospheric blockings are generally associated with large-scale high-pressure systems that interrupt west-to-east atmospheric flow in mid and high latitudes. Blockings cause several days of quasi-stationary weather conditions, and therefore can result in monthly or seasonal climate anomalies and extreme weather events on the affected regions. In this paper, the long-term coupled CERA-20C reanalysis data from 1901 to 2010 are used to evaluate the links between blocking events over the North Atlantic north of 35° N, and atmospheric and oceanic modes of climate variability on decadal time scales. This study indicates more frequent and longer lasting blocking events than previous studies using other reanalyses products. A strong relationship was found between North Atlantic blocking events and North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO) and Baffin Island–West Atlantic (BWA) indices, in fall, winter and spring. More blocking events occur during the negative phases of the NAO index and positive phases of the BWA mode. In some situations, the BWA patterns provide clearer links with the North Atlantic blocking occurrence than with the NAO alone. The correlation between the synchronous occurrences of AMO and blocking is generally weak, although it does increase for a lag of about 6–10 years. Convergent cross mapping (CCM) furthermore demonstrates a significant two-way causal effect between blocking occurrences and the NAO and BWA indices. Finally, while we find no significant trends in blocking frequencies over the last 110 years in the Northern Hemisphere, these events become longer lasting in summer and fall, and more intense in spring in the North Atlantic.
Keywords: Gachon_Philippe

A database of Holocene temperature records for north‐eastern North America and the north‐western Atlantic - Van Bellen, Simon; De Vernal, Anne; To, Anna; Ouellet‐Bernier, Marie‐Michèle; Roy, Natasha; ClimHuNor Members (Geoscience Data Journal, 2020)
Abstract Centennial‐to‐millennial temperature records of the past provide a context for the interpretation of current and future changes in climate. Quaternary climates have been relatively well studied in north‐east North America and the adjacent Atlantic Ocean over the last decades, and new research methods have been developed to improve reconstructions. We present newly inferred reconstructions of sea surface temperature for the north‐western Atlantic region, together with a compilation of published temperature records. The database thus comprises a total of 86 records from both marine and terrestrial sites, including lakes, peatlands, ice and tree rings, each covering at least part of the Holocene. For each record, we present details on seasons covered, chronologies and information on radiocarbon dates and analytical time steps. The 86 records contain a total of 154 reconstructions of temperature and temperature‐related variables. Main proxies include pollen and dinocysts, while summer was the season for which the highest number of reconstructions were available. Many records covered most of the Holocene, but many dinocyst records did not extend to the surface, due to sediment mixing, and dendroclimate records were limited to the last millennium. The database allows for the exploration of linkages between sea ice and climate and may be used in conjunction with other palaeoclimate and palaeoenvironmental records, such as wildfire records and peatland dynamics. This inventory may also aid the identification of gaps in the geographic distribution of past temperature records thus guiding future research efforts.
Keywords: Gachon_Philippe

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.